HUBUNGAN ASUPAN MIKRONUTRIEN DAN INDEKS MASSA TUBUH DENGAN KEJADIAN SINDROM PREMENSTRUASI PADA MAHASISWI UNIVERSITAS UDAYANA - Putri, Devana Prayitno; Sutiari, Ni Ketut (ARCHIVE OF COMMUNITY HEALTH; Vol 11 No 3 (2024): Desember 2024DO - 10.24843/ACH.2024.v11.i03.p01, 2025)
Premenstrual syndrome is collection of physical, emotional and psychological symptoms a few days before menstruation with a prevalence of 80-95% in Indonesia. This study aims to determine the relationship between micronutrient intake and body mass index with the incidence of premenstrual syndrome in Udayana University female students. The research design was cross sectional with a sample of 104 female students. This research uses primary and secondary data. The data studied were intake of micronutrients (vitamin B6, vitamin D, calcium, magnesium) and body mass index. Data collection was carried out through weighing and measuring body mass index, as well as interviews using identity questionnaires, nutritional status questionnaires, sPAF, and SQ-FFQ. The sample selection was carried out in three stages using purposive sampling and simple random sampling techniques. Data analysis was performed using univariate and bivariate. Most students have normal BMI (71.2%) and experience premenstrual syndrome (43.3%). Vitamin B6 is significantly associated with the incidence of premenstrual syndrome (p=0.025). Intake of vitamin D, calcium, magnesium, and BMI weren’t associated with the incidence of premenstrual syndrome (p>0.05). Improvement of eating patterns in female students is carried out as an effort to prevent the occurrence of premenstrual syndrome. Keywords: Micronutrients, BMI, Premenstrual Syndrome